Echoes of british contributions to the celebrations of the fourth centenary of the discovery of the maritime route to India - Simões-Ferreira, Isabel (2017)
After the occupation problems arising from the Berlin conference (1884-85) which marked the European race for territories in Africa and the setbacks suffered by the British Ultimatum (1890), the commemorations of the Fourth Centenary of the Discovery of the Maritime Route to India (1898), organized by the Lisbon Geographical Society, gained a vital importance for Portugal’s self-esteem and for her recognition among nations. Our purpose is to interpret some of the British contributions to the celebrations of this event and analyze how the mythical and patriotic orientation of the Portuguese celebrations is recontextualized by British voices. Despite paying homage to the daring Portuguese mariners “who starting from the extreme west of Europe, opened a way across those ‘Seas never before navigated’ ”, these voices have to be read in the light of the logic of Anglocentric 'desire'. This is tantamount to saying that we are dealing, in late Victorian England, with speeches or narratives of the ‘real’ which express colonial beliefs, an unfaltering sense of mission and, as a consequence, are profoundly ideological and nationalistic.